Characterize southwestern United States pinon-juniper woodlands: seeing the "old" trees for the "young" forest - Jacobs, Brian Francis, author; Romme, William H., advisor (Colorado State University. Libraries, 2008)
Southwestern U.S. piñon pine and juniper woodlands are often represented as an expanding and even invasive vegetation type, a legacy of historic grazing and culpable in the degradation of western rangelands. Yet the extent and dynamics of piñon-juniper communities pre-dating intensive Euro-American settlement activities are poorly known or understood, while the intrinsic ecological, aesthetic, and economic values of old-growth woodlands are often overlooked. Historical changes in piñon juniper include two related, but poorly differentiated, processes: recent tree expansion into grass or shrub dominated (i.e., non-woodland) vegetation and thickening or infilling of savanna or mosaic woodlands pre-dating settlement. My work addresses the expansion pattern, modeling the occurrence of "older" savanna and woodland stands extant prior to 1850, in contrast to "younger" piñon juniper growth of more recent, post-settlement origin. I present criteria in the form of a diagnostic key for distinguishing "older", pre-Euro-American settlement woodlands from "younger" (post-1850) stands, and report results of predictive modeling and mapping efforts within the Four Corners states (i.e., Arizona, Colorado, New Mexico, and Utah) of the American southwest in piñon juniper types characterized by Pinus edulis and three associated junipers (Juniperus osteosperma, J. monosperma, J. scopulorum). Selected models suggest a primary role for soil moisture in the current distribution of "old" versus "young" piñon juniper stands. Pre-settlement era woodlands are shown to occupy a discrete ecological space, defined by the interaction of effective (seasonal) moisture with landform setting and fine-scale (soil-water) depositional patterns. "Older" stands are generally found at higher elevations or on skeletal soils in upland settings, while "younger" stands (often dominated by one-seed juniper, Juniperus monosperma) are most common at lower elevations or in productive, depositional settings. Areas of the southwestern U.S. with strong monsoonal (summer moisture) patterns appear to have been the most susceptible to historical woodland expansion, but even here the great majority of extant piñon juniper has pre-settlement origins (although widely thickened and infilled historically) and old-growth structure is not uncommon in appropriate upland settings. Modeling at broad regional scales can enhance a general understanding of piñon juniper ecology, while predictive mapping of local areas has potential to provide products useful for land management.
Keywords: juniper; Juniperus monosperma; Juniperus osteosperma; Juniperus scopulorum; Pinus edulis; pinyon; predictive modeling; restoration; topo-climate; woodlands; ecology; forestry